Non-statistical fragmentation of large molecules in collisions with atoms. (November 2015) - Stockett, M H; Adoui, L; Anderson, E K; Chen, T; Chesnel, J-Y; de Ruette, N; Gatchell, M; Giacomozzi, L; Huber, B A; Kulyk, K; Maclot, S; Rousseau, P; et al.
Abstract: Non-statistical fragmentation processes are important when Polycyclic Aromatic Hydrocarbon (PAH) molecules, fullerenes, or other large molecules collide with atoms at center- of-mass energies from a few tens to a few hundreds of eV. The typical result is the prompt, billiard-ball-like knockout of single atoms (CH x -loss). This is distinct from the well-known statistical fragmentation patterns of these molecules, which are dominated by H- and C2 H2 -loss for PAHs and C2 -loss for fullerenes. We have explored the role of non-statistical fragmentation of PAHs and fullerenes in a series of experimental and theoretical studies. In general, the yield of non-statistical fragments depends sensitively on their stability against secondary statistical fragmentation following knockout.